90.4k views
3 votes
(-8/5) x - 6 =-54
Solve

User Nfgl
by
5.2k points

2 Answers

7 votes
We simplify the equation to the form, which is simple to understand
(-8/5)x-6=-54

Reorder the terms in parentheses
(-1.6x)-6=-54

Remove unnecessary parentheses
-1.6x-6=-54

We move all terms containing x to the left and all other terms to the right.
-1.6x=-54+6

We simplify left and right side of the equation.
-1.6x=-48

We divide both sides of the equation by -1.6 to get x.
x=30
Hope this helped
User Kludge
by
5.9k points
6 votes

( - 8/5) x -6 = -54

-8/5 x -6 = -54

multiply both sides of the equation by 5

-8 x -30= -270

-8 x -30 = - 270

move constant to the right side and change its sign

-8 x = -270 + 30

-8 x = - 270 + 30

calculate the sum

-8 x = -240

divide both sides of the equation by -8

then you have your awnser


x = 30


i hope this helps!

User Myol
by
5.4k points